THE COUNSELOR PERSONALITY OF BASED-CULTURE MAJA LABO DAHU - M. Affan Iskandar (Prodi Bimbingan Konseling Universitas Negeri Manado, 2021)
Society is a place for culture, in culture there are values ​​that are used as guidelines for behavior, as well as counselors and counselees, each of which has a culture. Success in the counseling process cannot be separated from the personality of a counselor, even the personality of the counselor is a necessity so that it is felt to be very important. So far, the personality theory of counselors has mostly been based on theories from the West, which basically have differences, so they are not automatically applied in Indonesia, which in fact has a variety of cultures. The purpose of this article is to see how the concept of the counselor's ideal personality from a cultural perspective uses a library research method in which data are obtained from books, documents, magazines, and historical stories that are relevant to the problems discussed. There are six values ​​in the Maja labo dahu cultural concept that can be used as the counselor's ideal personality concept, namely: Cua Iu Ade Angi, Kaco'o Angi, Konco'i Bandai Weki Ndai, Romobo Ro Kou, Tedi, and Tohompara Nahu Sura Dou Labo